Al-Hajj Umar Taal or El-Hajj Malik El-Shabazz (Malcolm X)? Case Studies on Islam and Interreligious Pan-African Unity - Jimmy Earl Butts (Religions)
A comparison between the function of Islam in the lives of Al-Hajj Umar Taal and El-Hajj Malik El-Shabazz (Malcolm X) suggests that Shabazz’s example of translating his Islamic obligations into the secular philosophy of Pan-Africanism reflects more promise toward the interest of interreligious Pan-African unity. During the nineteenth century, figures like Edward Blyden and Duse Muhammad Ali both presented the compatibility of Islam with Pan-Africanism. However, the practical examples of the steps needed to obtain interreligious unity require continued exploration. The author begins with an examination of the question of jihad and the “religious other” in Islam as understood by some. Secondly, the author focuses on Umar Taal to explore the way his understanding of Islam affected his relationship with both Muslim and non-Muslim Africans he encountered in nineteenth-century West Africa. Subsequently, the author analyzes how Malik El-Shabazz understood Islam to relate to the quest for Pan-Africanism. Using concepts from the critical theory of religion, the author will argue that Shabazz’s determinate negation of elements of his religious commitments that might hinder unity among people of African descent is instructive for the construction of an interreligious Pan-African unity.